2012
DOI: 10.1016/j.preteyeres.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Diverse types of ganglion cell photoreceptors in the mammalian retina

Abstract: Photoreceptors carry out the first step in vision by capturing light and transducing it into electrical signals. Rod and cone photoreceptors efficiently translate photon capture into electrical signals by light activation of opsin-type photopigments. Until recently, the central dogma was that, for mammals, all phototransduction occurred in rods and cones. However, the recent discovery of a novel photoreceptor type in the inner retina has fundamentally challenged this view. These retinal ganglion cells are intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 129 publications
(247 reference statements)
1
66
0
3
Order By: Relevance
“…Vertebrate ipRGCs do not have elaborate membrane protrusions (Sand et al, 2012) of the kind found in rhabdomeric photoreceptors, leading to less efficient photon capture. In agreement with this finding, ipRGCs are less sensitive than most invertebrate visual photoreceptors (Do and Yau, 2015).…”
Section: Rhabdomeric Photoreceptorsmentioning
confidence: 99%
“…Vertebrate ipRGCs do not have elaborate membrane protrusions (Sand et al, 2012) of the kind found in rhabdomeric photoreceptors, leading to less efficient photon capture. In agreement with this finding, ipRGCs are less sensitive than most invertebrate visual photoreceptors (Do and Yau, 2015).…”
Section: Rhabdomeric Photoreceptorsmentioning
confidence: 99%
“…mammal | melanopsin | phototransduction | gain control I t has become clear over the past decade that the mammalian retina contains another photoreceptor class besides rods and cones, consisting of a subpopulation of retinal ganglion cells (RGCs) that are intrinsically photosensitive (ipRGCs) by virtue of their expression of the visual pigment, melanopsin (1)(2)(3)(4)(5)(6)(7). In mouse, these cells have been distinguished into subtypes: M1 through M5 (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…In mouse, these cells have been distinguished into subtypes: M1 through M5 (4)(5)(6)(7). The first three can be visualized immunocytochemically with antibodies against melanopsin (with the M1 cells showing a higher melanopsin level than the other two) and have distinct morphological and physiological properties (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). M4 and M5 cells cannot be labeled by conventional immunocytochemistry, presumably because they have too little melanopsin, and are generally visualized more indirectly (12) [most recently, however, M4 cells have been revealed by immunofluorescence after signal amplification (15)].…”
mentioning
confidence: 99%
“…Their classifications, morphological, and physiological characteristics have been reviewed from different point of views [15][16][17][18][19]. Not all ipRGCs are in one retinal layer [16,20,21].…”
Section: Resultsmentioning
confidence: 99%
“…A distinction has been made on whether they were placed in the ganglion cell layer (known as orthotopic or normal placed) or in the inner nuclear layer (known as displaced). Moreover, five subtypes (M1-M5) of ipRGCs have been identified each with different soma size and dendrites stratifications [16,17,19]. Every subtypes projects to specific retino-recipient brain structures or central targets, e.g., SCN, olivary pretectal nucleus (OPN), and dorsal lateral geniculate nucleus (dLGN).…”
Section: Resultsmentioning
confidence: 99%